Water and Nitrogen Distribution Uniformity for Different Drip-lengths under Drip Irrigation System - Kumar, Mukesh; Rajput, T. B. S.; Patel, Neelam (Journal of Agricultural Engineering, 2014)
A field experiment was conducted at the research farm of Water Technology Centre, Indian Agricultural Research Institute, New Delhi during 2010 to study the effect of different drip-lengths (lateral) (25, 50, 75 and 100 m) and system operating pressures (0.5, 1.0 and 1.5 kg.cm-2) on water and nitrogen distribution uniformity under drip irrigation system. The varying drip lengths and system operating pressures significantly (P<0.01) affected coefficient of variation and distribution uniformity of the drip irrigation system. Highest distribution uniformity for both irrigation water (97.4%) and urea (97.8%) were observed at 1.5 kg.cm-2 operating pressure with 25 m long laterals. The lower values of urea distribution uniformity (93.0%) were recorded at 0.5 kg.cm-2 pressure with 100 m long drip line. Considering the system uniformity coefficient with drip lengths at different system operating pressures and an engineering approach towards the performance of the system for using drip-line, 50 m length was found appropriate for operation at 0.5 kg.cm-2 pressure. However, better performance of the drip up to 100 m lateral length was obtained at pressures of 1 and 1.5 kg.cm-2. Water and fertilizer distribution uniformity decreased with increase in lateral length, while it increased with increase in system operating pressure.